An interface evaporator with amphiphilic micro-nano structure and its preparation method and application

Under acidic conditions, the interface evaporator that uses static adsorption to build a porous structure solves the problem of hydrophobic regulation of the existing light and thermal evaporation materials, significantly improves the evaporation rate, and reduces efficient ionic concentrations in seawater dilute.

CN118851314BActive Publication Date: 2025-01-24HAINAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411076758.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-01-24
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

The hydrophilicity regulation of existing photothermal evaporation materials is difficult to meet both hydrophilic and hydrophobic needs, which affects the evaporation rate and reaction rate.

Method used

The interface evaporator with a micro -nano structure with two lips is used. Under acidic conditions, the electrostatic adsorption effect of reducing oxygenne and starch -like primary fibers is used to build a porous structure. Its hydrophobicity.

Benefits of technology

The evaporation rate of the photothermal interface evaporator is significantly improved (up to 2.398kg·m-2·h-1), and the ion concentration in artificial seawater can be reduced to meet drinking water standards during the seawater desalination process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851314B_ABST
    Figure CN118851314B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an interface evaporator with an amphiphilic micro-nano structure, wherein graphene oxide sheets are weighed and dispersed in an acidic aqueous solution to obtain a graphene oxide dispersion, the graphene oxide dispersion is then added to an amyloid fibril solution for stirring, and then a hydrazine hydrate solution is added for reduction reaction to obtain a SPI-AFs@rGO pre-gel solution of soybean protein isolate amyloid fibrils combined with reduced graphene oxide; thereafter, glutaraldehyde is added for further cross-linking to obtain a SPI-AFs@rGO-Gel hydrogel. The method of the invention utilizes the electrostatic adsorption of reduced graphene oxide and amyloid fibrils under acidic conditions to construct a soybean protein isolate amyloid fibril-based aerogel with a porous structure, and at the same time regulates the hydrophilicity of the amyloid fibrils at a micro-nano scale to improve the evaporation rate of the photothermal interface evaporator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photothermal evaporation materials, and in particular to an interface evaporator with an amphiphilic micro-nano structure, and a preparation method and application thereof. Background Art

[0002] Desalination of seawater is a feasible way to obtain large amounts of fresh water. However, most of the current methods of desalination use membrane distillation and reverse osmosis, which consume a large amount of fossil energy and are not conducive to environmental sustainability. Solar interfacial evaporation is low-cost and high-efficiency, and is a very promising method for producing fresh water. A solar interfacial evaporator is a device that uses solar energy to drive water evaporation. Through efficient photothermal conversion, it converts light energy into thermal energy and concentrates the heat at the water-air interface, thereby maximizing the evaporation efficiency. It has potential application prospects in the fields of seawater desalination, wastewater treatment, or salt extraction. Therefore, it has attracted the interest of many researchers.

[0003] For example, Chinese patent CN202311487004.2 discloses a solar interfacial evaporator based on amyloid plant protein fiber aerogel, and its preparation method and application. The aerogel is obtained by fiberizing soy protein isolate powder and using directional freezing and steam cross-linking strategies; then, a polypyrrole photothermal coating is grown in situ on the surface of the aerogel by in situ polymerization to obtain a solar interfacial evaporator, which improves the evaporation rate and solar evaporation efficiency to a certain extent. However, it is found that the hydrophilicity of the photothermal evaporation material used has a direct impact on the product and substrate in the process of mass transfer, thereby affecting the transmission rate and reaction rate. The current hydrophilicity and hydrophobicity regulation mainly regulates the same material by hydrophobicity and hydrophilicity, and it is impossible to achieve both hydrophilicity and hydrophobicity by one means. In addition, the material is regulated by technical means such as metal ion induction and in situ growth on the membrane surface, but the regulation process of this method is complicated and requires more stringent conditions and environment during operation.

[0004] Therefore, it is necessary to develop an interfacial evaporator with adjustable hydrophilicity and hydrophobicity and an amphiphilic micro-nano structure and a preparation method thereof. Summary of the invention

[0005] In view of this, the present invention provides an interface evaporator with an amphiphilic micro-nano structure to solve the problem of low evaporation rate of the existing evaporator due to the inability to adjust its hydrophilicity and hydrophobicity.

[0006] On the one hand, the present invention adopts a preparation method of an interfacial evaporator with an amphiphilic micro-nano structure, comprising the following steps: weighing a certain amount of starch-like soy protein isolate powder and incubating it to obtain a starch-like protein fibril solution, weighing graphene oxide sheets and dispersing them in an acidic aqueous solution to obtain a graphene oxide dispersion, then adding the graphene oxide dispersion to the starch-like protein fibril solution and stirring, and then adding a hydrazine hydrate solution for reduction reaction to obtain a SPI-AFs@rGO pre-gel solution of starch-like soy protein isolate fibrils combined with reduced graphene oxide; and then adding glutaraldehyde for further cross-linking to obtain a SPI-AFs@rGO-Gel hydrogel, wherein the mass ratio of graphene oxide to starch-like soy protein isolate powder is 0.2%-1%.

[0007] Preferably, the amount of hydrazine hydrate solution is 15 μL, and the mass concentration is 60-90%.

[0008] Preferably, the amyloid fibril solution is prepared by the following method: weigh 5 g of amyloid soy protein isolate powder and add it to 95 mL of deionized water to obtain a SPI starch suspension solution with a mass concentration of 5 wt.%; adjust the solution pH to 2 with 6.0 M HCl, then add 0.58 g of NaCl and seal it, stir it at 250 rpm for 8 h in an oil bath at 85 ° C, take it out and immediately put it in an ice bath for 10 min, and then incubate it at 25 ° C for 3 days to obtain an amyloid fibril solution.

[0009] Preferably, the reduction reaction condition is stirring at 80° C. and 300 rpm for 20 h.

[0010] Another aspect of the present invention provides an interface evaporator having an amphiphilic micro-nano structure.

[0011] Another aspect of the present invention provides an application of an interface evaporator with an amphiphilic micro-nano structure in the preparation of seawater desalination materials.

[0012] The preparation method of the interface evaporator with an amphiphilic micro-nano structure provided by the present invention is adopted. Under acidic conditions, the electrostatic adsorption of reduced graphene oxide and amyloid fibrils is utilized to regulate the hydrophilicity and hydrophobicity of amyloid fibrils at the micro-nano scale, and a soy protein isolate amyloid fibril-based aerogel with a porous structure is constructed, which significantly improves the evaporation rate of the photothermal interface evaporator (up to 2.398 kg·m -2 ·h -1 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1FTIR spectra of graphene oxide (GO), SPI-AFs-Gel and SPI-AFs@rGO-Gel prepared by using different mass ratios of GO and amyloid soy protein isolate powder (SPI) in Example 1 and Example 2;

[0014] Figure 2 (a) Composite solutions containing different mass ratios of GO and SPI in the precursor; (b) TEM image of 5wt.% SPI-AFs pure solution; (c) TEM image of the composite solution with a GO and SPI input ratio of 0.4%; (d) TEM image of the composite solution with a GO and SPI input ratio of 1%;

[0015] Figure 3 (ae) Actual pictures of hydrogels prepared using GO and SPI composite solutions with different mass ratios; (fj)) corresponding SEM pictures;

[0016] Figure 4 The interface contact angle test results of the SPI-AFs@rGO-Gel hydrogel composite material prepared by adding different mass ratios of GO and SPI composite solutions in Example 1, Example 2 and Comparative Example 1;

[0017] Figure 5 Ca in seawater before and after solar desalination using SPI-AFs@rGO-Gel interfacial evaporator 2+ , K + Mg 2+ and Na + Ion concentration. DETAILED DESCRIPTION

[0018] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0019] The single-layer graphene oxide sheet in the embodiment of the present invention was purchased from Suzhou Carbon Graphene Technology Co., Ltd.

[0020] Embodiment 1: A method for preparing an interface evaporator having an amphiphilic micro-nano structure, comprising the following steps:

[0021] S101: Preparation of amyloid fibril solution: First, defatted soybean meal was added to the NaOH solution at a feed ratio of 1:15 (w / w), stirred for 2 hours, and then centrifuged for 30 minutes to remove insoluble substances. The pH of the supernatant was adjusted to 4.5 with 2M HCl, and then the precipitate was collected by centrifugation. The precipitate was washed twice with deionized water, and the soy protein solution was collected and freeze-dried to obtain SPI soy protein isolate powder. Subsequently, 5g of SPI amyloid soy protein isolate powder was weighed and added to 95mL of deionized water to obtain a SPI starch suspension solution with a mass concentration of 5wt.%; the solution pH was adjusted to 2 with 6.0M HCl, and then 0.58g of NaCl was added and sealed, and stirred at 250rpm for 8h in an oil bath at 85℃, and immediately immersed in ice water for 10min to terminate the self-assembly process after being taken out, and then placed at 25℃ for 3 days to obtain amyloid fibril (SPI-AFs) solution;

[0022] S102: weigh 30 mg of a single-layer graphene oxide sheet (GO), and disperse it in 5 mL of a hydrochloric acid aqueous solution with a pH of 2 by an ultrasonic device to obtain a graphene oxide dispersion; then add the above-mentioned graphene oxide dispersion to the SPI-AFs solution of step S101 and stir for 2 h, then add 15 μL of a hydrazine hydrate solution with a mass concentration of 80%, keep the temperature at 80°C, and stir at a speed of 300 rpm for 20 h to fully reduce the graphene oxide to reduced graphene oxide (rGO), so as to obtain a SPI-AFs@rGO pregel solution of soy protein isolate amyloid fibrils combined with reduced graphene oxide; wherein the mass ratio of graphene oxide (GO) to soy protein isolate powder (SPI) is 0.6%;

[0023] S103: Add 6.72 mL of the corresponding amount of glutaraldehyde solution to the SPI-AFs@rGO pregel solution, add it into the mold, and crosslink for 12 hours to obtain the hydrogel SPI-AFs@rGO-Gel of soy protein isolate starch-like fibrils composited with reduced graphene oxide.

[0024] Example 2: The difference between Example 2 and Example 1 is that the amount of graphene oxide added is adjusted (10 mg, 20 mg, 40 mg and 50 mg), that is, the mass of graphene oxide and soy protein isolate powder input is 0.2%, 0.4%, 0.8% and 1% respectively.

[0025] In another embodiment, the concentration of the SPI starch suspension solution is 2% to 10%.

[0026] In another embodiment, the concentration of the hydrazine hydrate solution is 60% to 90%.

[0027] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that 6.72 ml of a corresponding amount of glutaraldehyde solution is directly added to the SPI-AFs pre-hydrogel in step S101, added to a mold, and cross-linked for 12 hours to obtain a hydrogel of soy protein isolate amyloid fibrils, wherein the mass ratio of graphene oxide (GO) to soy protein isolate powder (SPI) is 0%.

[0028] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that step S102 does not undergo redox treatment with hydrazine hydrate solution, and the hydrogel prepared by composite synthesis of soy protein isolate amyloid fibrils and graphene oxide has only 1.137 kg·m -2 ·h -1 Its evaporation rate is relatively improved compared with that without adding graphene oxide, but the evaporation rate of the hydrogel prepared by the composite material of soybean protein isolate amyloid fibrils and reduced graphene oxide is still low.

[0029] The hydrogel SPI-AFs@rGO-Gel prepared in the above example was characterized and tested, and the results are as follows:

[0030] (1) Infrared tests were performed on graphene oxide (GO), SPI-AFs-Gel, and SPI-AFs@rGO-Gel prepared with different mass ratios of GO and SPI. Figure 1 As shown in the infrared results, the characteristic absorption peaks located in the amide I, amide II and amide III regions can be clearly seen, indicating that the soybean protein isolate has been successfully prepared into amyloid fibrils through the self-assembly of fiberization. In addition, the intact retention of the characteristic peaks also shows that the structure of the amyloid fibrils has not been destroyed during the entire preparation, compounding and regulation of the material. Compared with the infrared spectrum of GO, the infrared spectrum of SPI-AFs@rGO-Gel shows a peak at 1370cm -1 -OH and 1051cm -1 The intensity of the characteristic absorption peak of CO was reduced to a certain extent, indicating that GO was successfully reduced to rGO by hydrazine hydrate. This shows that the successfully reduced graphene oxide on the SPI-AFs@rGO-Gel material was composited on the soy protein isolate amyloid fibrils through electrostatic adsorption, and there was no obvious change to the original structure.

[0031] (2) Figure 2 a is a display diagram of the SPI-AFs@rGO pre-gel solution prepared by adding different mass ratios of GO:SPI in Example 1 and Example 2. It can be clearly seen from the picture that with the increase of GO input, that is, the continuous increase of rGO content after in situ reduction, the color of the SPI-AFs stock solution gradually darkens, indicating that the compounding of different contents of rGO has a significant effect on the color change of the original fiber solution. Figure 2 From the TEM image of the composite solution corresponding to bd, we can see that high-density SPI-AFs are adsorbed on the surface of rGO due to electrostatic effect, which not only indicates that SPI-AFs are successfully composited on rGO to obtain a micro-nano structure, but also confirms the integrity of rGO, proving that the structure of graphene is not destroyed by the composite SPI-AFs.

[0032] (3) Figure 3 ae are actual pictures of SPI-AFs@rGO-Gel hydrogels prepared with different mass ratios of GO and SPI in Example 1 and Example 2. The color change trends of the hydrogels shown in the actual pictures are basically consistent, indicating that making the solution into hydrogel has no obvious change on the material itself. Figure 3 fj SEM image of the hydrogel prepared, which shows the pore size and distribution inside the SPI-AFs@rGO-Gel hydrogel prepared by adding GO and SPI solutions in different mass ratios. It can be observed from the figure that the pore size is mainly concentrated around 50μm, but does not show any regular changes in the pore size due to the different rGO contents, indicating that the amount of graphene added has little effect on the stability of the hydrogel macrostructure.

[0033] (4) The experimental results of the interface contact angle test of the SPI-AFs@rGO-Gel hydrogel prepared by adding different mass ratios of GO in Example 1 and Example 2 are as follows: Figure 4 The results show that with the continuous increase of rGO content, the interface contact angle also gradually increases from 17.4° (0.2% rGO) to 105.3° (1.0% rGO), and the hydrophilicity changes significantly. As the input GO increases, that is, the composite content of rGO obtained after in-situ reduction increases, the material becomes more hydrophobic. This shows that rGO can effectively regulate the hydrophilicity and hydrophobicity of SPI-AFs@rGO-Gel, and an interface evaporator with amphiphilic micro-nano structure can be obtained.

[0034] (5) The water evaporation rate of the SPI-AFs@rGO-Gel hydrogel prepared by adding GO in different mass proportions in Example 1 and Example 2 was tested. From the result data in Table 1, it can be seen that with the gradual increase of rGO content, the evaporation rate of the hydrogel shows a trend of first increasing and then decreasing. Compared with the hydrogel without graphene treatment, the evaporation rate is significantly improved. In the SPI-AFs@rGO-Gel prepared by adding GO:SPI mass ratio of 0% to 0.6% in the precursor, the reasonably constructed and optimized amphiphilic structure not only satisfies the rapid and sufficient transport of water to the photothermal evaporation interface, but also appropriately reduces the heat conduction to the water body, which is beneficial to the thermal management of the entire system and the improvement of the photothermal conversion efficiency, thereby improving the photothermal evaporation rate. However, in the SPI-AFs@rGO-Gel of 0.6% to 1.0%, due to excessive hydrophobicity and insufficient hydrophilicity, there is a significant lack of water supply, which reduces the photothermal evaporation rate.

[0035] Table 1 Evaporation rate of SPI-AFs@rGO-Gel hydrogel composites prepared using different GO and SPI input mass ratios

[0036]

[0037] (6) By Figure 5 It can be seen that the hydrogel prepared by using the soy protein isolate amyloid fibrils and reduced graphene oxide prepared in Example 1 can reduce the concentration of various ions in artificial seawater to below the drinking water standard specified by the World Health Organization after 30 days and is available for use.

[0038] In summary, by adopting the preparation method of an interfacial evaporator with an amphiphilic micro-nano structure provided by the present invention, under acidic conditions, the electrostatic adsorption effect of reduced graphene oxide and amyloid fibrils is utilized to construct a porous structure to adjust the pore size of soybean protein isolate amyloid fibril-based aerogel, and at the same time, the hydrophilicity and hydrophobicity of amyloid fibrils are regulated at the micro-nano scale to improve the evaporation performance of the photothermal interfacial evaporator.

[0039] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an interface evaporator having an amphiphilic micro-nano structure, characterized in that: The following steps are involved: Amyloid fibril solution was obtained by incubating amyloid soy protein isolate powder (SPI) solution, graphene oxide sheets (GO) were weighed and dispersed in acidic aqueous solution to obtain graphene oxide dispersion, and then the graphene oxide dispersion was added into the amyloid fibril solution and stirred, and then hydrazine hydrate solution was added for reduction reaction to obtain SPI-AFs@rGO pregel solution of soy protein isolate amyloid fibrils (SPI-AFs) combined with reduced graphene oxide (rGO); glutaraldehyde was added for further cross-linking to obtain SPI-AFs@rGO-Gel hydrogel, wherein the mass ratio of graphene oxide to amyloid soy protein isolate powder was 0.2%-1%.

2. The method for preparing an interface evaporator having an amphiphilic micro-nano structure according to claim 1, characterized in that: The mass ratio of graphene oxide to starch-like soy protein isolate powder is 0.6%.

3. The method for preparing an interface evaporator having an amphiphilic micro-nano structure according to claim 1, characterized in that: The hydrazine hydrate solution is used in an amount of 15 μL, and has a mass concentration of 60-90%.

4. The method for preparing an interface evaporator with an amphiphilic micro-nano structure according to claim 1, characterized in that: The amyloid fibril solution is prepared by the following method: 5 g of amyloid soy protein isolate powder is weighed and added into 95 mL of deionized water to obtain a starch suspension solution with a mass concentration of 5 wt.%; The pH of the solution was adjusted to 2 with 6.0 M HCl, and then 0.58 g NaCl was added and sealed. The mixture was stirred at 250 rpm in an oil bath at 85°C for 8 h. After being taken out, it was immediately placed in an ice bath for 10 min and incubated at 25°C for 3 days to obtain an amyloid fibril solution.

5. The method for preparing an interface evaporator with an amphiphilic micro-nano structure according to claim 1, characterized in that: The reduction reaction conditions are stirring at 80° C. and 300 rpm for 20 h.

6. An interfacial evaporator with an amphiphilic micro-nano structure, prepared by the method according to any one of claims 1 to 5.

7. Use of the interfacial evaporator with an amphiphilic micro-nano structure according to claim 6 in the preparation of seawater desalination materials.

Citation Information

Patent Citations

  • A solar interface evaporator based on starch-like plant protein fiber aerogel and its preparation method and application

    CN117599435B

  • Method and system for removing insoluble solids mid-evaporation from a corn dry milling process

    CA3091409A1

  • Waste-reused aerogel for solar sewage purification and production method thereof

    CN109847660A